Distribution of scleractinian corals in Taklong Island, Guimaras for the period December 2001 to January 2002. - Bodoso, Daniel Penturas
The study of the distribution of scleractinian or hard corals genera was done in Taklong Island, Nueva Valencia, Guimaras from December 2001 to January 2002 employing the line-intercept method. Twenty-one (21) genera were identified within three survey sites with and average coal cover of 33.4% for all the study sites. Porites was the dominant genera and was followed by other massive colonial corals such as Goniastrea Favites, pavona, and Platygra and by the branching genus Acropora.